Keanekaragaman dan Dominansi Vegetasi Pohon Pada Habitat Eulipoa wallacei di Hutan Hii Desa Haruku Kabupaten Maluku Tengah - Picarima, Reynita; Kakisina, Pieter; Sahertian, Dece Elisabeth (Universitas Hasanuddin, 2024)
The Hii Forest of Haruku Village is where Eulipoa wallacei lays eggs. The Hii Forest is overgrown with tree vegetation that Eulipoa wallacei uses as a perch, a place to forage for food and to protect itself from predators. This study aimed to determine the diversity and dominance of tree vegetation in the habitat of Eulipoa wallacei in the forest. The method used in this study is the quadratic method by placing sample plots randomly based on public information about the location of Eulipoa wallacei. The results showed 29 plant species belonging to 2 classes, 13 orders, and 22 families. The Diversity Index and Dominance Index of tree vegetation in the habitat of Eulipoa wallacei in Hii Forest showed diversity in the medium category and dominance in the low category. Eulipoa wallacei's habitat is used for perching, foraging, and protecting itself from predators.